Effect of Cu-chitosan Composite Based Seed Coating on Seed Quality Enhancement and Antifungal Activity - Sangeetha, B. M.; Bhat, N. Bharati; Prasad, R. D.; Kumar, V. Dinesh; Supriya, K.; Chandrika, K. S. V. P. (International Journal of Economic Plants, 2025)
The experiment was conducted during September to November, 2023 at ICAR-IIOR, Rajendranagar, Hyderabad, Telangana (500030), India to develop and evaluate the Cu-chitosan based composite as seed treatment material and its antifungal activity against soil borne pathogen, Sclerotium rolfsii Sacc. and compatibility of Cu-chitosan composite with biocontrol agent Trichoderma, in order to develop a sustainable approach to enhance seedling growth in groundnut. Chitosan, a natural biopolymer has a significant attention in agriculture due to its versatile properties. Seed coating with chitosan improves germination rate and seedling quality by providing conducive microenvironment and protection against soil borne pathogens. The Cu-chitosan composite solution prepared with 4% chitosan and cross-linker C, showed better film forming ability with stickiness and complete solubility in the water compared to other combinations. Coating of groundnut seeds with Cu-chitosan composite prepared with 4% chitosan resulted in the highest germination percentage and seedling vigour of the seedlings compared to the control. In vitro studies revealed that Chitosan based composite (Cu-chitosan composite C) exhibited 100% compatibility with the biocontrol agent, Trichoderma harzianum Th4d. Further, it also inhibited the mycelial growth of S. rolfsii to the extent of 44.81%. These findings indicate that Cu-chitosan composite can be potentially utilized in combination with the biocontrol agent, Trichoderma harzianum Th4d to provide enhanced protection to the seeds against soil borne pathogens and it also improves the seedling growth and development.